Breaking through the bottleneck in the promotion of artificial intelligence in agriculture: an analysis of the moderating role of individual’s heterogeneity among farmers in Shandong Province - Cao Kai; Wang Ping; Kong Siyu; Zhang Chunzhen (Frontiers in Sustainable Food Systems)
The application of agricultural artificial intelligence is of great significance for improving agricultural productivity, reducing labor demand, and mitigating agricultural pollution, serving as a crucial path for achieving sustainable agricultural development. The study aims to deeply analyze the influencing factors on agricultural artificial intelligence of its usage intention in Shandong Province. Based on the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT), this study constructs an extended model and employs questionnaire surveys and Partial Least Squares Structural Equation Modeling (PLS-SEM) technology for research. The research results show that performance expectancy, effort expectancy, government support, and social influence are the key factors affecting the usage intention of agricultural artificial intelligence, accessibility and satisfaction are key mediating variables linking exogenous variables to outcome variables. Additionally, the age, educational background, and work experience play important roles in the moderation model. This indicates that there are significant differences in the usage intention of agricultural artificial intelligence among groups with different ages, educational backgrounds, and work experiences. By customizing promotion strategies, it is expected to accelerate the transformation of agriculture toward intelligence and promote the achievement of sustainable agricultural development goals.